Performance and Employer Stock in 401(k) Plans - Huberman, Gur; Sengmueller, Paul (Review of Finance, 2004)
Abstract Participants in 401(k) retirement plans violate the basic principle of diversification by investing significant fractions of their savings in their employers' equity. This paper characterizes investors' active changes to their company stock investment over time by analyzing new inflows and transfers. The average investor seems to base active changes on salient information, paying attention to past returns, volatility, and business performance. Past returns, over a three-year horizon, predict higher inflow allocations and transfers, whereas volatility and business performance only have a weak effect. The sensitivity to past returns is asymmetric, with investors reacting more strongly to positive and above-S&P500 returns.